2013
DOI: 10.1007/s11626-013-9611-7
|View full text |Cite
|
Sign up to set email alerts
|

Derivation and characterization of cell cultures from the skin of the Indo-Pacific humpback dolphin Sousa chinensis

Abstract: The marine mammalian Indo-Pacific humpback dolphin, once widely lived in waters of the Indian to western Pacific oceans, has become an endangered species. The individual number of this dolphin has significantly declined in recent decades, which raises the concern of extinction. Direct concentration on laboratorial conservation of the genetic and cell resources should be paid to this marine species. Here, we report the successful derivation of cell lines form the skin of Indo-Pacific humpback dolphin. The cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 21 publications
2
15
0
Order By: Relevance
“…Primary cells lifespan is limited to several passages and limits the long-term availability of these cells for further research. Similarly, Jin et al, [ 16 ] found that fibroblast cell cultures morphology and growth noted rapid at early passages, but later showed obvious growth arrest at higher passages. To overwhelm this issue, gene transfer of SV40 early regions has been widely used to escape the Hayflick limit [ 17 , 22 ].…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…Primary cells lifespan is limited to several passages and limits the long-term availability of these cells for further research. Similarly, Jin et al, [ 16 ] found that fibroblast cell cultures morphology and growth noted rapid at early passages, but later showed obvious growth arrest at higher passages. To overwhelm this issue, gene transfer of SV40 early regions has been widely used to escape the Hayflick limit [ 17 , 22 ].…”
Section: Discussionmentioning
confidence: 84%
“…It was previously reported that the normal diploid somatic cells of cetacean species contain 21 or 22 pairs of chromosomes [ 8 ], which can show multiple stages of chromosomes. Similarly, Jin et al [ 16 ] showed 44 chromosomes in Chinese white dolphin fibroblast cells. Cetacean chromosomes numbers often have 42 to 44 and may appear metacentric, submetacentric, telocentric and sub-telocentric [ 11 ].…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…G r o w t h o f H u W a 1 a n d 2 Jin et al (2013) reports the establishment of humpback dolphin fibroblast cultures and assessed 3-5 days of proliferation until cells reached confluency when passaged 1:3. The same study observed reduced proliferation starting from P10 and finally senescence with P17.…”
Section: R E C O V E R Y a F T E R C R Y O P R E S E R V A T Io Nmentioning
confidence: 99%